Change in adverse event reporting following immunization of hepatitis B vaccine among infants between 2013 to 2020 before and after the vaccine administration law in China - Wang, Chao; Huang, Ninghua; Lu, Qing-Bin; Black, Steven; Liang, Xiaofeng; Cui, Fuqiang (Frontiers in Immunology, 2022)
Background Hepatitis B vaccine (HepB) has been routinely recommended as part of the immunization program in China and has had a satisfactory safety and effectiveness profile in protecting infants from hepatitis B virus infection. We evaluated the surveillance sensitivity and changes over time of AEFI reports related to HepB among infants based on the consistent national data before and after the introduction of vaccine administration law (LAW) from 2013 to 2020 in China. Methods AEFI records were extracted from the Chinese National AEFI Surveillance System from 2013 to 2020. According to the proportion of different kinds of HepB vaccines distributed, the annual administration data of the most distributed HepB produced by Bio-Kangtai and its corresponding adverse reaction reports were collected and analyzed. We categorized the time interval into the pre-LAW period (2013 to 2017), transition period (2018 to 2019), and LAW period (2020) to demonstrate the impact of LAW on the surveillance patterns of AEFIs. Results The annual AEFI rates increased from 3.1/100,000 to 14.8/100,000 over this period in total. The rate ratio for the post-LAW period and pre-LAW period was 2.19 (95%CI: 2.10, 2.29). Common reactions occupied 87.6% of the total reported AEFIs whose rate was recorded as 7.9/100,000. Rare reactions occupied 9.1% of the total AEFIs showing an average rate of 0.8/100,000, of which anaphylaxis accounted for over 80%, with the rate ratio of the transition period and LAW period as 1.36 (95%CI:1.22, 1.52) and 1.14 (95%CI:0.95, 1.35), respectively. Children receiving more than one vaccine showed a higher proportion of fever, anaphylaxis, and febrile convulsions, which were suggested to be a result of vaccine co-administration vaccines, such as the DPT and Polio vaccine. Conclusion Most reactions were mild and self-limited and the rates of rare more serious events remained stable. The LAW has largely increased the surveillance capability and sensitivity on AEFIs of HepB and also contributes to enhancing public confidence in HepB immunization. Hepatitis B vaccination is a safe and effective means of preventing the complications of hepatitis B disease and continuous standardized AEFI investigation and assessment of causal association should be maintained.